Motivasi Belajar Siswa Terhadap Hasil Belajar pada Mata Pelajaran Olahraga Bola Voli SMA - Sukowati, Anton; Aji Suryo Putro, Waskito; Anwar, Saiful (Jurnal Muara Olahraga, 2024)
The type of research uses a quantitative approach. The type of research is correlational. This research is a study involving a population of 45 students. Data were collected using a research instrument in the form of a questionnaire. Of the 30 questions tested, there were 23 valid questions with a reliability value of 0.903. The data analysis technique used was product moment correlation. The results of the study showed that: (1) the average/mean learning motivation of class X students of SMA Negeri 3 Raja Ampat was 70.77 or in the moderate category, (2) the average/mean learning outcomes of class X students of SMA Negeri 3 Raja Ampat was 69.00 or in the moderate category, and (3) there is a positive and significant relationship between learning motivation and learning outcomes of the Volleyball Sports Subject for Class X Students of SMA Negeri 3 Raja Ampat. This is indicated by the large value of r count which is greater than r table (0.490>0.286) and a significance value of 0.000, which means less than 0.05 (0.000<0.05)